Bridging Legal Ambiguity and Customary Legitimacy: Governance of Village Boundaries in Multicultural Rural Indonesia - Muhammadnor Fitri; Samahuddin (Program Studi Ilmu Pemerintahan, FISIP - Universitas Halu Oleo, 2026)
This study examines the dynamics of customary and administrative village boundary management in Kambiyain and Auh Villages, Tebing Tinggi District, Balangan Regency, from a governance perspective. The research focuses on three key aspects: legal clarity in boundary determination, community participation in boundary arrangements, and coexistence through tolerance and mutual recognition between the Dayak and Banjar communities. Using a qualitative descriptive approach, data were collected through in-depth interviews with customary leaders, village officials, community members, and local government actors, supported by field observations and document analysis of maps and relevant policies. Data analysis involved reduction, presentation, and interpretive conclusion. The findings show that formal legal clarity has not been achieved due to the absence of a definitive Regent Regulation. However, customary boundaries under Dayak Pitap tradition provide strong social legitimacy. Participation occurs through informal deliberation and traditional leadership, but remains weakly integrated into formal mechanisms. Social relations between communities remain stable, marked by tolerance and the absence of open conflict despite differing systems. The study concludes that social harmony and customary legitimacy sustain governance under legal gaps. Policy implications highlight the need for local governments to accelerate boundary formalization through participatory mechanisms that recognize customary boundaries and strengthen institutional integration. These findings support adaptive policies that balance administrative authority, culturalbrecognition, and long-term conflict prevention in multicultural village governance contexts today.